Improving reliability of energy equipment under operational conditions - Smetankina, Natalia; Misiura, Serhii; Misiura, Ievgeniia (Громадська наукова організація "Всеукраїнська асамблея докторів наук з державного управління", 2026)
The purpose of this research is to develop methods and means of diagnosing the vibration state and resource of the responsible nodes of power units and their use to assess the damage and resource of the most stressed elements and nodes of turbo machines and power equipment to increase the reliability and safety of their operation.
Keywords: energy equipment; reliability; repair ability; methods and means of diagnosing; vibration state